Influence of Hydrocarbon Chain Branching on Foam Properties of Olefin Sulfonate with FoamScan. Issue 6 (2nd September 2016) - Wang, Yong; Liu, Xiaochen; Zhou, Yawen; Niu, Jinping
Abstract: The influence of surfactant structure on foam properties of internal olefin sulfonate (IOS) and alpha olefin sulfonate (AOS) in aqueous solutions was estimated from measurements of the foamability, foam stability, and foam morphology, as obtained from conductivity and image analyses techniques. It was found that the foamability and foam stability of C16–18 AOS are higher compared to that of C16–18 IOS, indicating that hydrocarbon chain branching decreases the foamability and foam stability. The foamability and foam stability are enhanced with increasing surfactant concentration, which increases the adsorbed quantity of surfactant molecules at the air–water interface. The influence of hydrocarbon chain branching on foam morphology was also investigated. It was found that foam cells produced by branched chain C16–18 IOS are larger than the foam cells generated by straight chain C16–18 AOS.